Diversity and abundance of storage pest in rice warehouses in Klang, Selangor, Malaysia - Syarifah Zulaikha Syed Ahmad; Madihah Halim; Nor Atikah A.R.; Salmah Yaakop (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Insect’s pest infestation on rice product cause a serious damage either in quantitative or qualitative aspect. This paper assesses the abundance and diversity of insects pest of stored products in rice warehouses, through a study in three rice warehouse (Jasa, Tenggara, Target Lane) in Klang Selangor, Malaysia. Investigations recorded four main insect species in all the warehouses are Oryzaephilus surinamensis, Tribolium castaneum, Sitophilus oryzae and Cadra cautella. Oryzaephilus surinamensis showed the highest abundance in all warehouse with total 47403 individuals (97%), T. castaneum with 431 individuals (0.88%), C. cautella with 760 individuals (1.56%) and S. oryzae with the lowest abundance (11 individuals; 0.02%). The Shannon-Weiner index shows that highest insects diversity was in Tenggara warehouse (Shannon’s, H’ = 0.28), while Target Lane were the lowest (Shannon’s, H’=0.11). The information on insect’s pest diversity in rice warehouses is very useful to implementation of management and controlling insect’s pest infestation in stored rice grains.